The Use of Photosynthetic Bacteria and Jakaba in Promoting the Growth of Post-Acclimatization Kepok Bung Banana Plants - Srilestari, Rina; Wijayani, Ari; Suwardi, Suwardi; Pratiwi, Krisnandini Wahyu (International Journal Labs, 2025)
This research investigates the use of photosynthetic bacteria (PSB) and Jakaba liquid organic fertilizer (POC) as sustainable alternatives to chemical fertilizers for post-acclimatization Kepok Bung banana plants. Using a field experiment with a split-plot design, we tested three concentrations of PSB (10 ml/L, 15 ml/L, and 20 ml/L) and three concentrations of Jakaba POC (10 ml/L, 20 ml/L, and 30 ml/L) to determine their effects on plant growth parameters. Results demonstrated a significant interaction between PSB and Jakaba concentrations, with the combination of PSB at 10 ml/L and Jakaba POC at 10 ml/L yielding optimal results. This treatment produced a 37% increase in root number, 42% improvement in plant fresh weight, and 45% increase in dry weight compared to less effective treatment combinations. The enhanced growth can be attributed to improved photosynthetic efficiency, better nutrient absorption, and stimulated root development. These findings provide banana farmers with a practical, environmentally sustainable alternative to chemical fertilizers that effectively supports plant growth during the critical post-acclimatization phase while reducing environmental degradation associated with conventional fertilization methods.